Outcomes from a community-based, participatory lay health advisor HIV/STD prevention intervention for recently arrived immigrant Latino men in rural North Carolina, USA - Rhodes, Scott D. (2009)
BACKGROUND: Latinos in the United States are at increased risk for HIV and sexually transmitted disease (STD) infection. We evaluated the efficacy of a pilot, lay health advisor (LHA) intervention designed to increase condom use and HIV testing among Latino men. METHODS: Fifteen LHAs (mean age=35.6; range 23–60 years) from 15 Latino soccer teams were trained and worked with their teammates for 18 months. Another 15 teams served as the control group. Data were collected at baseline and 18-months post-LHA training from a random sample of teammates from intervention and control teams. RESULTS: Data were collected from 222 men (mean age=29 years) who participated in one of the 30 teams. Relative to the control condition, participants in the intervention reported more consistent condom use in the 30 days preceding follow-up (unadjusted analysis, intervention, 65.6% vs. control, 41.3%; P<.001). Participants in the intervention were more likely to report condom use (adjusted odds ratio=2.3; CI=1.2–4.3) and HIV testing (adjusted odds ratio=2.5; CI=1.5–4.3). CONCLUSIONS: LHA interventions for Latino men that are developed in partnership with community members, rely on male-centered intrapersonal networks, and are culturally congruent can enhance preventive behaviors and may reduce HIV infection.